Improved Synthesis of Anxiolytic, Anticonvulsant, and Antinociceptive α2/α3-GABA(A)-ergic Receptor Subtype Selective Ligands as Promising Agents to Treat Anxiety, Epilepsy, and Neuropathic Pain - Li, Guanguan; Golani, Lalit K.; Jahan, Rajwana; Rashid, Farjana; Cook, James M. (Synthesis, 2018)
An improved synthesis of the anxiolytic, anticonvulsant, and antinociceptive compounds: Hz-166, and its bioisosteres 1,2,4-oxadiazole (MP-III-080) and 1,3-oxazole (KRM-II-81) were synthesized in higher yields and with more facile purification methods (crystallization, etc.) in multigram quantities without column chromatography. In the synthesis of KRM-II-81, an alternative procedure was employed using the selective reducing reagent, potassium diisobutyl-tert-butoxyaluminum hydride (PDBBA), to prepare the desired C(3)-aldehyde in the absence of N(5)–C(6) imine reduction in good yield on a 20 gram scale.
Keywords: GABAAR; benzodiazepines; anxiety; epilepsy; neuropathic pain; large scale; imine; selective reduction